Towards green cities: the impact of bus-priority lanes on emission control for highly congested metropolitan areas during peak times - Szamek, Levi; Abanto Graffman, Daniel; Kitzinger, Maximiliane; Lautenbach, Sven; Zipf, Alexander (Zenodo, 2025)
This study evaluates public transport accessibility in Lima, Peru, and assesses the potential impact of implementing bus priority lanes. Using multimodal network modeling and open-source data, accessibility to points of interest is compared across different travel scenarios. Results highlight significant gaps in Lima’s current system and demonstrate how targeted infrastructure improvements can enhance access, reduce car dependency, and support sustainable urban mobility.